Effects of Calcination Temperatures on Photocatalytic Activity of Ordered Titanate Nanoribbon/SnO2 Films Fabricated during an EPD Process. (18th August 2011) - Zhao, Li; Ran, Jingrun; Shu, Zhan; Dai, Guotian; Zhai, Pengcheng; Wang, Shimin
Abstract : Ordered titanate nanoribbon (TNR)/SnO2 films were fabricated by electrophoretic deposition (EPD) process using hydrothermally prepared titanate nanoribbon as a precursor. The formation mechanism of ordered TNR film on the fluorine-doped SnO2 coated (FTO) glass was investigated by scanning electron microscopy (SEM). The effects of calcination temperatures on the phase structure and photocatalytic activity of ordered TNR/SnO2 films were investigated and discussed. The X-ray diffraction (XRD) results indicate that the phase transformation of titanate to anatase occurs at 400°C and with increasing calcination temperature, the crystallization of anatase increases. At 600°C, the nanoribbon morphology still hold and the TiO2 /SnO2 film exhibits the highest photocatalytic activity due to the good crystallization, unique morphology, and efficient photogenerated charge carriers separation and transfer at the interface of TiO2 and SnO2 .